Extraction, characterization of polyphenols from certain medicinal plants and evaluation of their antioxidant, antitumor, antidiabetic, antimicrobial properties, and potential use in human nutrition - Mueed, Abdul; Shibli, Sahar; Al-Quwaie, Diana A.; Ashkan, Mada F.; Alharbi, Mona; Alanazi, Humidah; Binothman, Najat; Aljadani, Majidah; Majrashi, Kamlah Ali; Huwaikem, Mashael; Abourehab, Mohammed A. S.; Korma, Sameh A.; et al. (Frontiers in Nutrition, 2023)
Dietary medicinal plants are among the most sought-after topics in alternative medicine today due to their preventive and healing properties against many diseases. This study aimed to extract and determine the polyphenols from indigenous plants extracts, i.e., Mentha longifolia, M. arvensis, Tinospora cordifolia, Cymbopogon citratus, Foeniculum vulgare, Cassia absus, Camellia sinensis, Trachyspermum ammi, C. sinensis and M. arvensis, then evaluate the antioxidant, cytotoxicity, and antimicrobial properties, besides enzyme inhibition of isolated polyphenols. The tested medicinal plants' polyphenolic extracts (MPPE) exhibited the most significant antioxidant activity in DPPH, hydroxyl, nitric oxide, and superoxide radical scavenging methods because of the considerable amounts of total polyphenol and flavonoid contents. UHPLC profile showed twenty-five polyphenol complexes in eight medicinal plant extracts, categorized into phenolic acids, flavonoids, and alkaloids. The main polyphenol was 3-Feroylquinic acid (1302 mg/L), also found in M. longifolia, C. absus, and C. sinensis, has a higher phenolic content, i.e., rosmarinic acid, vanillic acid, chlorogenic acid, p-coumaric acid, ferulic acid, gallic acid, catechin, luteolin, 7-O-neohesperideside, quercetin 3,7-O-glucoside, hesperidin, rutin, quercetin, and caffeine in the range of (560–780 mg/L). At the same time, other compounds are of medium content (99–312 mg/L). The phenolics in C. sinensis were 20–116% more abundant than those in M. longifolia, C. absus, and other medicinal plants. While T. cordifolia is rich in alkaloids, T. ammi has a lower content. The MTT assay against Caco-2 cells showed that polyphenolic extracts of T. ammi and C. citratus had maximum cytotoxicity. While M. arvensis, C. sinensis, and F. vulgare extracts showed significant enzyme inhibition activity, C. sinensis showed minor inhibition activity against α-amylase. Furthermore, F. vulgare and C. sinensis polyphenolic extracts showed considerable antibacterial activity against S. aureus, B. cereus, E. coli, and S. enterica. The principal component analysis demonstrated clear separation among medicinal plants' extracts based on their functional properties. These findings prove the therapeutic effectiveness of indigenous plants and highlight their importance as natural reserves of phytogenic compounds with untapped potential that needs to be discovered through advanced analytical methods.